2020
DOI: 10.1371/journal.pone.0237345
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis polyclonal infections through treatment and recurrence

Abstract: Background Mixed/polyclonal infections due to different genotypes are reported in Tuberculosis. The current study was designed to understand the fate of mixed infections during the course of treatment and follow-up and its role in disease pathogenesis. Methods Sputum samples were collected on 0,1,2,3,6,12 and 24 months from 157 treatment-naïve patients, cultures subjected to Drug-Susceptibility-testing (MGIT 960), spoligotyping, MIRU-VNTR and SNP genotyping. All isolated colonies on thin layer agar (7H11) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…However it disagrees with [29] who reported an association between mixed MTB infection and age and sex. In addition, [30] also reported strong association between having mixed MTB infection and CAS1_Delhi lineage (Lineage 3) which disagrees with this ndings. The difference in these ndings could be attributed to the geographical location where the study was done since the different MTB lineages are geographically located except Lineage 4 which seems to be widely distributed [31].…”
Section: Discussioncontrasting
confidence: 64%
“…However it disagrees with [29] who reported an association between mixed MTB infection and age and sex. In addition, [30] also reported strong association between having mixed MTB infection and CAS1_Delhi lineage (Lineage 3) which disagrees with this ndings. The difference in these ndings could be attributed to the geographical location where the study was done since the different MTB lineages are geographically located except Lineage 4 which seems to be widely distributed [31].…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study points out to the mixed or polyclonal infections in India that may occur due to infection by more than one genotypes during treatment, making drug resistance even a bigger nuisance. 74 While some reports discuss Manu ancestral lineage as an artefact due to co-infection by strains of Lineage 2 and 4, we are not in a position to comment, as this study did not examine any co-infection or polyclonal infections. 75 , 76 …”
Section: Discussionmentioning
confidence: 70%
“…However it disagrees with Pang et al (2015) [ 29 ] who reported an association between mixed MTB infection and age and sex. In addition, Pandey et al (2020) [ 30 ] also reported strong association between having mixed MTB infection and CAS1_Delhi lineage (Lineage 3) which disagrees with this findings. The difference in these findings could be attributed to the geographical location as Lineage 4 is the dominant lineage in Uganda.…”
Section: Discussionmentioning
confidence: 77%